Mewujudkan Pendidikan Berkualitas: Pendekatan Manajemen Berbasis Nilai Islami - Amaliah Fitriani Noor; Anggra Prima; Usfandi Haryaka (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
The planning, arranging, staffing, and supervision of every aspect of education in Islamic institutions are all part of the systematic operations known as Islamic Education Management. Curriculum design, staff and teaching staff management, student management, facility and financial management, community connections, and the creation of a work culture that supports learning are all starting points. For Islamic educational institutions to remain viable and advance, Islamic education management is crucial. Islamic educational institutions will be able to maintain their relevance, quality, and beneficial social impact with the support of effective administration. We must appropriately comprehend and implement the idea of Islamic-based educational administration if we are to meet the anticipated learning objectives. As a result, we need to examine this concept's consequences and significance in greater detail.